Art therapy and music therapy as psychopedagogical resources: the benefits of intersectoriality in the quality of life of elderly people living in a philanthropic home in Western Pará (Research, Society and Development, 2023)
Aging is a natural development that all living beings go through, consisting of a programmed genetic deterioration that affects the ability of cells to divide, renew and regenerate (cellular aging). Thus, body movements are reduced and increased attention is required. Thus, this work aims to show the importance of art therapy and music therapy in long-stay institutions to promote quality of life and provide an experience for the elderly who live in the philanthropic home. Therefore, this study is an experience report based on the Arco de Maguerez. In which it started on June 6, 2022 with the purpose of observing reality and ended on August 22, 2022, in which the implementation of these alternative therapies resulted in the contribution of health promotion to the elderly who live in a philanthropic home in the West of Pará. Therefore, the inclusion of art therapy and music therapy come as an alternative methodology that collaborate in improving the quality of life of the elderly through paintings, drawings and even musical ambiance.